Hardening components and hardening agents

JP2026166320APending Publication Date: 2026-10-14KANEKA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025059189
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0015】 本発明によれば、優れた熱解体性を有する硬化性組成物及びその硬化物が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166320000001
    Figure 2026166320000001
  • Figure 2026166320000002
    Figure 2026166320000002
Patent Text Reader

Abstract

The present invention provides a curable composition having excellent thermal decomposition properties and a cured product thereof. [Solution] The curable composition contains (A) an oxyalkylene polymer having reactive silicon groups, (B) a (meth)acrylic acid ester polymer having reactive silicon groups, and (C) unexpanded thermal expandable particles. The content of (C) unexpanded thermal expandable particles is 25 parts by weight or more per 100 parts by weight of the total of (A) the oxyalkylene polymer having reactive silicon groups and (B) the (meth)acrylic acid ester polymer having reactive silicon groups.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a curable composition having thermal decomposition properties and a cured product thereof. [Background technology]

[0002] Disassemblable adhesives are known in which the adhesive strength of the bonded parts decreases when subjected to stimuli such as heating, allowing the bonded parts to be easily separated. In recent years, the development of disassemblable adhesives has been progressing from the perspective of efficient use of resources and recycling.

[0003] Patent Document 1 describes a method for obtaining a heat-decomposable adhesive that has sufficient adhesive strength when bonded, but whose adhesive strength decreases when heated, making it easy to disassemble, by combining a moisture-crosslinkable polymer and heat-expandable particles. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] International Publication No. 2024 / 132795 [Overview of the project] [Problems that the invention aims to solve]

[0005] The present invention aims to provide a curable composition having excellent thermal decomposition properties and a cured product thereof. [Means for solving the problem]

[0006] (1) The curable composition according to the present invention contains (A) an oxyalkylene polymer having a reactive silicon group, (B) a (meth)acrylic acid ester polymer having a reactive silicon group, and (C) unexpanded thermally expandable particles. The content of (C) is 25 parts by weight or more with respect to 100 parts by weight of the total of (A) and (B).

[0007] (2) In (1), (C) may be a thermally expandable microcapsule in which a volatile expanding agent is contained within the outer shell.

[0008] (3) In (1) or (2), the expansion start temperature of (C) may be 70°C or higher.

[0009] (4) In any one of (1) to (3), the average particle size of (C) may be 9 μm or more.

[0010] (5) In any one of (1) to (4), the average particle size of (C) may be 24 μm or less.

[0011] (6) In any one of (1) to (5), the content of (C) may be 80 parts by weight or less with respect to a total of 100 parts by weight of (A) and (B).

[0012] (7) In any one of (1) to (6), (A) may be a mixture containing a polymer (A1) having a number average molecular weight of 10,000 or more and a polymer (A2) having a number average molecular weight of 5,000 or less.

[0013] In (8)(7), the weight ratio of (A1) to (A2) may be 5:95 to 95:5.

[0014] (9) The cured product according to the present invention is obtained by curing any one of the curable compositions (1) to (8). [Effects of the Invention]

[0015] According to the present invention, a curable composition having excellent thermal decomposition properties and a cured product thereof are provided. [Modes for carrying out the invention]

[0016] <Overview> The curable composition of the present invention contains (A) an oxyalkylene-based polymer having reactive silicon groups (hereinafter sometimes simply referred to as "polymer (A)"), (B) a (meth)acrylate ester-based polymer having reactive silicon groups (hereinafter sometimes simply referred to as "polymer (B)"), and (C) unexpanded thermally expandable particles (hereinafter sometimes simply referred to as "thermally expandable particles (C)").

[0017] The curable composition of the present invention can be suitably used, for example, as an adhesive for bonding parts of various industrial products such as automobiles, building materials, and electrical and electronic devices. The specific method of using the curable composition of the present invention as an adhesive is as follows.

[0018] (1) Bonding step The curable composition is cured to bond the members to each other. The polymer (A) and the polymer (B) form a crosslinked structure through hydrolysis and condensation occurring between the reactive silicon groups, whereby the curable composition cures to become a cured product. The hydrolysis and condensation occurring between the reactive silicon groups proceed, for example, due to moisture in the air.

[0019] (2) Disassembly step When the product obtained by bonding the members to each other is no longer needed, the members are disassembled by heating. The volume of the thermally expandable particles (C) increases upon heating, and the cured product becomes brittle, so that the members can be easily disassembled from each other.

[0020] The curable composition of the present invention exhibits excellent thermal disassembly properties, particularly when the content of the thermally expandable particles (C) is 25 parts by weight or more relative to a total of 100 parts by weight of the polymer (A) and the polymer (B).

[0021] Hereinafter, preferred embodiments of each component constituting the curable composition of the present invention will be described in order. Unless otherwise specified, each of the following components may be used alone or in combination of two or more kinds. In the present specification, "(meth)acrylic" means acrylic or methacrylic. Further, in the present specification, unless otherwise specified, "A to B" representing a numerical range means "A or more and B or less".

[0022] <Polymer (A)> Polymer (A) has reactive silicon groups.

[0023] Polymer (A) has a main chain structure and terminal structures bonded to the main chain structure. The main chain structure is a structure in which multiple constituent units derived from monomers are continuously bonded together. There may be one type of monomer or multiple types. The main chain structure may be linear or branched. The terminal structures are the parts located at the ends of polymer (A).

[0024] Reactive silicon groups can be present in the main chain structure and in the terminal structures. Furthermore, two or more reactive silicon groups may be present in a single terminal structure. In polymer (A), it is preferable that reactive silicon groups be present in the terminal structures because they readily react with moisture during the bonding process.

[0025] The reactive silicon group is not particularly limited as long as it is a silicon-containing group having a silanol group or a silicon-containing group capable of generating a silanol group by hydrolysis, and may be any known reactive silicon group. When the reactive silicon group generates a silanol group, polymer (A) is crosslinked by a condensation reaction between the silanol groups.

[0026] As the reactive silicon group, the group represented by the following formula (1) is preferred. -SiR 1 a X 3-a (1) In formula (1), R 1 Each of these independently comprises a substituted or unsubstituted hydrocarbon group having 1 to 20 carbon atoms, or R 0 It is a triorganosiloxy group represented as 3SiO-. In the triorganosiloxy group, there are three R 0 These are each an independent hydrocarbon group with 1 to 20 carbon atoms. 0 They may be the same or different. Each X is independently a hydroxyl group or a hydrolyzable group. a is 0, 1, or 2.

[0027] R in formula (1) 1 is preferably an alkyl group and an aryl group, more preferably a methyl group, an ethyl group and a phenyl group, further preferably a methyl group and an ethyl group, and particularly preferably a methyl group. When a plurality of R 1 are present in formula (1), the plurality of R 1 may be the same group, or may be a combination of two or more different groups.

[0028] The hydrolyzable group is not particularly limited, and may be a known hydrolyzable group. The hydrolyzable group is preferably an alkoxy group, an acyloxy group, a ketoximate group and an alkenyloxy group. An alkoxy group such as a methoxy group and an ethoxy group is more preferred because of mild hydrolyzability and easy handling. The methoxy group is particularly preferred in that the curability of the curable composition can be easily adjusted.

[0029] The reactive silicon group represented by formula (1) is not particularly limited, and a dimethoxymethylsilyl group and a trimethoxysilyl group are preferred because the polymer (A) can be easily synthesized. The trimethoxysilyl group and the methoxymethyldimethoxysilyl group are preferred in terms of excellent curability. The dimethoxymethylsilyl group is particularly preferred in terms of excellent stability.

[0030] The main chain structure of the polymer (A) includes a structural unit derived from oxyalkylene. Specific examples of the oxyalkylene include ethers such as oxyethylene, oxypropylene, oxybutylene, and oxytetramethylene. The oxyalkylene may be a combination of oxyethylene-oxypropylene, oxypropylene-oxybutylene, and the like.

[0031] As the main chain structure of the polymer (A), polyoxypropylene is particularly preferred. The polymer (A) having a main chain structure of polyoxypropylene is amorphous and has a relatively low viscosity, and the cured product tends to have excellent adhesiveness.

[0032] The ratio of oxyalkylene-derived constituent units to the total amount of constituent units in the main chain structure of polymer (A) is 50 mol% or more. The main chain structure of polymer (A) may contain other bonds besides ether bonds (such as urethane bonds and urea bonds), but from the viewpoint of obtaining a curable composition with excellent storage stability and workability, the ratio of oxyalkylene-derived constituent units to the total amount of constituent units in the main chain structure of polymer (A) is preferably 60 mol% or more, more preferably 70 mol% or more, and may be 80 mol% or more, 90 mol% or more, 99 mol% or more, or 100 mol%.

[0033] The method for synthesizing the main chain structure of polymer (A) is not particularly limited, and known synthesis methods may be used. Oxyalkylene polymers can be obtained, for example, by a ring-opening polymerization reaction of a cyclic ether compound using a polymerization catalyst in the presence of an initiator. Polymerization using a complex metal cyanide catalyst (see Japanese Patent Publication No. 46-27250, U.S. Patent No. 3278457, etc.) is particularly preferred due to its low manufacturing cost and the ability to obtain polymers with a narrow molecular weight distribution.

[0034] The method for introducing reactive silicon groups into the main chain structure of polymer (A) is not particularly limited and may be a known method. One example of a known method is to convert the terminal hydroxyl groups of a hydroxyl-terminated organic polymer into carbon-carbon unsaturated groups, and then to the carbon-carbon unsaturated groups, HSiR 1 a X 3-a One method is hydrosilylation using a hydrosilane represented by R. 1 X and a are the same as those in equation (1), respectively.

[0035] The number-average molecular weight (Mn) of polymer (A), as polystyrene-equivalent molecular weight in GPC (gel permeation chromatography), is preferably 800 to 100,000, more preferably 1,500 to 50,000, and particularly preferably 2,000 to 30,000. The weight-average molecular weight (Mw) of polymer (A), as polystyrene-equivalent molecular weight in GPC, is preferably 1,000 to 110,000, more preferably 2,000 to 55,000, and particularly preferably 2,400 to 33,000.

[0036] Specific examples of commercially available polymers (A) include various reactive silicon group-containing polyoxypropylene products such as Kaneka MS Polymer (registered trademark) and Kaneka Cyril (registered trademark). All of these commercially available polymers (A) are products of Kaneka Corporation. In addition, AGC Inc.'s Exester (registered trademark), WACKER's GENIOSIL (registered trademark), and RISUN POLYMER's STP can also be used as polymers (A).

[0037] The polymer (A) is preferably a mixture containing an oxyalkylene polymer (A1) with a number average molecular weight of 10,000 or more and an oxyalkylene polymer (A2) with a number average molecular weight of 5,000 or less. The curable composition tends to have improved thermal decomposition properties when it contains both a polymer with a large number average molecular weight (A1) and a polymer with a small number average molecular weight (A2). The presence of a polymer with a large number average molecular weight (A1) and a polymer with a small number average molecular weight (A2) in the curable composition causes a localized decrease in the crosslinking density of the cured product, and it is thought that stress concentration occurs when the volume of the thermally expandable particles (C) increases due to heating, which is one of the reasons for the improved thermal decomposition properties. The number average molecular weight of polymer (A1) is preferably 10,000 or more, more preferably 15,000 or more, even more preferably 20,000 or more, and particularly preferably 25,000 or more. The number-average molecular weight of polymer (A1) may be 30,000 or more, 35,000 or more, 40,000 or more, or 45,000 or more. The number-average molecular weight of polymer (A2) is preferably 5,000 or less, more preferably 4,500 or less, even more preferably 4,000 or less, and particularly preferably 3,500 or less. The number-average molecular weight of polymer (A2) may be 3,000 or less, 2,500 or less, 2,000 or less, 1,500 or less, or 1,000 or less.

[0038] The weight ratio of polymer (A1) to polymer (A2) is preferably 5:95 to 95:5, as an increase in the amount of one of the polymers is expected to improve decompositionability. A weight ratio of 50:50 to 90:10 is more preferable, 60:40 to 85:15 is even more preferable, and 70:30 to 80:20 is even more preferable. By setting the weight ratio of polymer (A1) to polymer (A2) as described above, it is believed that a curable composition with excellent thermal decompositionability can be obtained while maintaining appropriate adhesive strength as an adhesive.

[0039] <Polymer (B)> Polymer (B) has reactive silicon groups. The reactive silicon groups are not particularly limited as long as they can form siloxane bonds. The reactive silicon groups represented by formula (1) above are preferred. Polymer (B) has a main chain structure and terminal structures bonded to the main chain structure.

[0040] Reactive silicon groups can be present in the main chain structure and terminal structures. In polymer (B), it is preferable that reactive silicon groups be present in the terminal structures because they readily react with moisture during the bonding process.

[0041] The reactive silicon groups of polymer (B) may be the same as or different from the reactive silicon groups of polymer (A).

[0042] The main chain structure of polymer (B) contains constituent units derived from alkyl (meth)acrylate. Note that the monomers used to produce polymer (B) may also contain monomers other than alkyl (meth)acrylate.

[0043] Specific examples of alkyl acrylates include methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, n-decyl acrylate, n-undecyl acrylate, lauryl acrylate, n-tridecyl acrylate, myristyl acrylate, cetyl acrylate, stearyl acrylate, and behenyl acrylate.

[0044] Specific examples of alkyl methacrylates include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, n-decyl methacrylate, n-undecyl methacrylate, lauryl methacrylate, n-tridecyl methacrylate, myristyl methacrylate, cetyl methacrylate, stearyl methacrylate, and behenyl methacrylate.

[0045] The ratio of constituent units derived from alkyl (meth)acrylate to the total amount of constituent units of the main chain structure of polymer (B) is preferably 50 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, and particularly preferably 90 mol% or more, and may be 99 mol% or more or 100 mol%.

[0046] Alkyl (meth)acrylate esters having an alkyl group with 1 to 30 carbon atoms are defined by the following formula (2): CH2=CR b1 COOR b2 (2) (In formula (2), R b1 R is a hydrogen atom or a methyl group. b2 (These are alkyl groups with 1 to 30 carbon atoms.) It is represented as follows.

[0047] In equation (2), R b2 Examples include alkyl groups with 1 to 30 carbon atoms, such as methyl group, ethyl group, n-propyl group, n-butyl group, tert-butyl group, 2-ethylhexyl group, lauryl group, n-tridecyl group, cetyl group, and stearyl group. b2 The number of carbon atoms in the alkyl group is more preferably 1 to 20.

[0048] The number-average molecular weight (Mn) of polymer (B) is preferably 500 to 20,000, more preferably 1,500 to 18,000, as polystyrene-equivalent molecular weight in GPC. The weight-average molecular weight (Mw) of polymer (B) is preferably 500 to 25,000, more preferably 1,500 to 20,000, as polystyrene-equivalent molecular weight in GPC.

[0049] The main chain structure of polymer (B) can be produced by conventional vinyl polymerization methods. Examples of vinyl polymerization methods include solution polymerization by radical reaction and bulk polymerization. However, vinyl polymerization is not limited to these methods. The above polymerization reaction is typically carried out at 50-150°C in the presence of monomers, radical initiators, chain transfer agents, and solvents. The conditions for the polymerization reaction are not limited to the above conditions.

[0050] The method for introducing reactive silicon groups into the main chain structure of polymer (B) is not particularly limited and may be a known method. An example of a known method is a method in which a compound having an ethylenically unsaturated double bond and a reactive silicon group is copolymerized with an alkyl (meth)acrylate represented by formula (2).

[0051] The amount of polymer (B) used in the curable composition is not particularly limited. In the curable composition, the weight ratio of polymer (A) to polymer (B) is preferably 95:5 to 5:95, more preferably 90:10 to 20:80, even more preferably 80:20 to 30:70, and particularly preferably 60:40 to 80:40.

[0052] <Thermally expandable particles (C)> Thermally expandable particles (C) are particles that have the property of expanding when heated. Preferably, thermally expandable particles (C) are thermally expandable microcapsules. Thermally expandable microcapsules are tiny hollow particles in which a volatile expanding agent, such as a low-boiling point solvent, is encapsulated inside an outer shell. When thermally expandable particles (C) are heated, the outer shell softens and the encapsulated volatile expanding agent volatilizes, causing the outer shell to expand due to the resulting pressure, thereby increasing the particle volume.

[0053] The outer shell of the thermally expandable microcapsules is preferably formed from a thermoplastic resin. Examples of thermoplastic resins include vinyl polymers and copolymers thereof such as ethylene, styrene, vinyl acetate, vinyl chloride, vinylidene chloride, acrylonitrile, methacrylonitrile, butadiene, and chloroprene; polyamides such as nylon 6 and nylon 66; and polyesters such as polyethylene terephthalate. Acrylonitrile copolymers are preferred because they are less permeable to the encapsulated volatile expanding agent.

[0054] Examples of volatile expanding agents encapsulated inside thermally expandable microcapsules include hydrocarbons with 3 to 8 carbon atoms such as propane, propylene, butene, n-butane, isobutane, isopentane, neopentane, n-pentane, hexane, heptane, octane, and isooctane; halides of methane such as methyl chloride and methylene chloride; chlorofluorocarbons such as CCl3F and CCl2F2; tetraalkylsilanes such as tetramethylsilane and trimethylethylsilane; and low-boiling point liquids such as petroleum ethers.

[0055] Commercially available thermally expandable particles (C) can also be used. Examples of commercially available products include Nouryon's microspheres (product names: Expansion 051 DU 40, Expansion 043 DU 80, Expansion 920 DU 20), Matsumoto Oil & Fat Pharmaceutical's microspheres (product names: F-20D, F-30D, F-40D, FN-100D, FN-100MD, FN-100SD, FN-100SSD, FN-180D, FN-180SD, FN-180SSD, F-190D, F-260D), and Kureha's microspheres (product names: H850D, H880D, S2340D, S2640D).

[0056] The expansion initiation temperature of the thermally expandable particles (C) is not particularly limited, but is preferably 70°C or higher, more preferably 90°C or higher, even more preferably 100°C or higher, and especially preferably 110°C or higher. In this specification, the expansion initiation temperature refers to the temperature at which the expansion curve (a graph with temperature on the horizontal axis and particle volume on the vertical axis) begins to rise (the particle volume begins to increase) when the unexpanded thermally expandable particles (C) are heated at a rate of 20°C per minute. This expansion curve is obtained by TMA (Thermomechanical Analysis) measurement. The expansion initiation temperature of the thermally expandable particles (C) may be 120°C or higher, 130°C or higher, 140°C or higher, 150°C or higher, 160°C or higher, 170°C or higher, 180°C or higher, or 190°C or higher. If the expansion initiation temperature of the thermally expandable particles (C) is 70°C or higher, it is particularly preferable because the thermally expandable particles (C) do not thermally expand during the curing of the curable composition, but thermally expand when heated during dismantling. The expansion initiation temperature of the thermally expandable particle (C) may be 300°C or lower, 250°C or lower, or 200°C or lower.

[0057] The average particle diameter of the thermally expandable particles (C) is preferably 5 μm or more, more preferably 9 μm or more, and also preferably 24 μm or less, more preferably 15 μm or less. If the average particle diameter of the thermally expandable particles (C) is too small or too large, sufficient thermal decomposition may not be obtained. Also, if the average particle diameter of the thermally expandable particles (C) is too large, sufficient adhesive strength as an adhesive may not be obtained. An average particle diameter of 9 to 15 μm is particularly preferred for the thermally expandable particles (C). When the average particle diameter of the thermally expandable particles (C) is within the above range, the thermal decomposition of the curable composition is good. The average particle diameter of the thermally expandable particles (C) is the median diameter (D(0.5)) value measured by low-angle laser light scattering.

[0058] The content of thermally expandable particles (C) is preferably 25 parts by weight or more, and more preferably 30 parts by weight or more, per 100 parts by weight of the total of polymer (A) and polymer (B). The content of thermally expandable particles (C) may be 40 parts by weight or more, or 50 parts by weight or more, per 100 parts by weight of the total of polymer (A) and polymer (B). Alternatively, the content of thermally expandable particles (C) is preferably 11% by weight or more, and more preferably 12% by weight or more, relative to the total solid content of the composition. The content of thermally expandable particles (C) may be 15% by weight or more, 16% by weight or more, 17% by weight or more, or 18% by weight or more, relative to the total solid content of the composition. When the content of thermally expandable particles (C) is 25 parts by weight or more, or 11% by weight or more, relative to the total of polymer (A) and polymer (B), the thermal decomposition properties of the curable composition are good. This is thought to be because, if the content of thermally expandable particles (C) is greater than or equal to the above value, the size of the thermally expandable particles (C) in the curable composition is sufficient to generate the stress necessary for demolition within the cured material.

[0059] Furthermore, the content of thermally expandable particles (C) is preferably 80 parts by weight or less, and more preferably 60 parts by weight or less, per 100 parts by weight of the total of polymer (A) and polymer (B). Alternatively, the content of thermally expandable particles (C) is preferably 27% by weight or less, and more preferably 21% by weight or more, relative to the total solid content of the composition. If the content of thermally expandable particles (C) is too high, the adhesive strength as an adhesive may be insufficient.

[0060] <Additives> The curable composition may contain additives in addition to polymer (A), polymer (B), and thermally expandable particles (C). Examples of additives include curing catalysts, fillers, adhesion promoters, plasticizers, solvents, diluents, thixotropic agents, antioxidants, light stabilizers, UV absorbers, property modifiers, tackifying resins, compounds containing epoxy groups, photocurable substances, oxygen-curable substances, epoxy resins and other resins, surface modifiers, foaming agents, curing modifiers, flame retardants, silicates, radical inhibitors, metal deactivators, phosphorus-based peroxide decomposers, lubricants, pigments, and antifungal agents.

[0061] Preparation of curable compositions The curable composition can be prepared as a one-component type, where all components are pre-mixed and sealed for storage, and then cured by moisture in the air after application. Alternatively, it can be prepared as a two-component type, where components such as a curing catalyst, filler, plasticizer, and water are mixed separately, and the mixture containing these components is mixed with a curable composition containing an oxyalkylene polymer (A), a (meth)acrylic acid ester polymer (B), and thermally expandable particles (C) before use. The one-component type is preferred in terms of workability.

[0062] Uses of curable compositions The curable composition can be suitably used as an adhesive for bonding parts of various industrial products, such as automobiles, building materials, and electrical and electronic equipment. As mentioned above, the curable composition has excellent thermal decomposition properties, so by using the curable composition as an adhesive, parts can be easily separated and disassembled by heating when recycling products or when re-bonding parts. The curable composition may also be used as a sealant. [Examples]

[0063] The present invention will be further explained below with reference to examples and comparative examples, but it is not limited to these examples.

[0064] (molecular weight) The number-average molecular weight Mn and weight-average molecular weight Mw were measured by GPC under the following conditions. Liquid delivery system: Tosoh HLC-8420GPC Column: Tosoh TSKgel SuperH series Solvent: THF Molecular weight: Polystyrene equivalent Measurement temperature: 40℃

[0065] (Average number of reactive silicon groups) The average number of reactive silicon groups per molecule of the polymer was calculated by NMR measurement.

[0066] [Synthesis of oxyalkylene polymers containing reactive silicon groups] <Synthesis of polymer (A1)> Using polyoxypropylene glycol with a number-average molecular weight of approximately 4,800 as an initiator, propylene oxide was polymerized with a zinc hexacyanocobaltate-grime complex catalyst to obtain polyoxypropylene (P-1) with a number-average molecular weight of 27,900 (end-group equivalent molecular weight of 17,700) and a molecular weight distribution Mw / Mn = 1.21, having hydroxyl groups at both ends. Subsequently, 1.0 molar equivalent of sodium methoxide in a 28% methanol solution was added to the hydroxyl groups of this hydroxyl-terminated polyoxypropylene (P-1). After removing methanol by vacuum defoliation, 1.8 molar equivalents of allyl chloride were further added to the hydroxyl groups of the polymer (P-1) to convert the terminal hydroxyl groups to allyl groups, and the unreacted allyl chloride was removed by vacuum defoliation. After mixing and stirring n-hexane and water with the obtained unpurified polyoxypropylene, the water was removed by centrifugation, and the metal salts in the polymer were removed by vacuum defoliation of the hexane from the resulting hexane solution. From the above steps, polyoxypropylene (Q-1) having allyl groups at its termini was obtained. To 500 g of this polymer (Q-1), 50 μL of platinum divinyldisiloxane complex solution (3% by weight isopropanol solution in terms of platinum) was added, and 9.6 g of trimethoxysilane was slowly added dropwise while stirring. After reacting the mixed solution at 100°C for 2 hours, the unreacted trimethoxysilane was removed under reduced pressure to obtain polyoxypropylene (A1) with a number average molecular weight of approximately 28,000 and trimethoxysilyl groups at its termini. Polymer (A1) was found to have an average of 1.7 trimethoxysilyl groups at each termini and an average of 3.4 trimethoxysilyl groups per molecule.

[0067] <Synthesis of polymer (A2)> Using polyoxypropylene glycol with a number-average molecular weight of approximately 4,800 as an initiator, propylene oxide was polymerized with a zinc hexacyanocobaltate-grime complex catalyst to obtain polyoxypropylene (P-2) with a number-average molecular weight of 3,000 (end-group equivalent molecular weight of 2,700) and a molecular weight distribution Mw / Mn = 1.16, having hydroxyl groups at both ends. Subsequently, 1.2 molar equivalents of sodium methoxide in a 28% methanol solution were added to the hydroxyl groups of this hydroxyl-terminated polyoxypropylene (P-2). After removing methanol by vacuum defoliation, an additional 1.5 molar equivalents of allyl chloride were added to the hydroxyl groups of the polymer (P-2) to convert the terminal hydroxyl groups to allyl groups, and the unreacted allyl chloride was removed by vacuum defoliation. To the obtained unpurified polyoxypropylene, n-hexane and water were mixed and stirred, and the water was removed by centrifugation. The metal salts in the polymer were removed by vacuum defoliation of the hexane from the resulting hexane solution. From the above steps, polyoxypropylene (Q-2) having allyl groups at the terminals was obtained. To 500 g of this polymer (Q-2), 50 μL of platinum divinyldisiloxane complex solution (3 wt% isopropanol solution in terms of platinum) was added, and 6.9 g of trimethoxysilane was slowly added dropwise while stirring. After reacting the mixed solution at 100°C for 2 hours, the unreacted trimethoxysilane was removed under reduced pressure to obtain polyoxypropylene (A2) with a number average molecular weight of approximately 5,000 and trimethoxysilyl groups at the terminals. Polymer (A2) was found to have an average of 0.7 trimethoxysilyl groups at each terminal and an average of 1.4 trimethoxysilyl groups per molecule.

[0068] [Synthesis of (meth)acrylic acid ester polymers containing reactive silicon groups] <Synthesis of polymer (B)> A mixture consisting of 300 g of methyl methacrylate, 115 g of 2-ethylhexyl acrylate, 46 g of γ-methacryoxypropyltrimethoxysilane, and 140 g of isobutyl alcohol (IBA) was dissolved in 11.5 g of azobis-2-methylbutyronitrile as a polymerization initiator. This solution was added dropwise to 200 g of IBA heated to 105°C in a reaction vessel over 5 hours. Polymerization was then carried out for 2 hours to obtain an isobutyl alcohol solution of (meth)acrylic acid ester copolymer (B) having trimethoxysilyl groups, with a solid content of 60% by weight and a number average molecular weight of 2,200.

[0069] [Preparation of curable compositions] (Thermally expandable particles) The details of the unexpanded thermally expandable particles used in the following examples and comparative examples are as follows. (C-1): Manufactured by Nouryon, product name: Expansion 051 DU 40, average particle size D (0.5): 9~15 μm (measured by low-angle laser scattering method) (C-2): Manufactured by Nouryon, product name: Expansion 043 DU 80, average particle size D (0.5): 16~24 μm (measured by low-angle laser scattering method) (C-3): Manufactured by Nouryon, product name: Expansion 920 DU 20, average particle size D (0.5): 5~9 μm (measured by low-angle laser scattering method)

[0070] <Example 1> 60 parts by weight of oxyalkylene polymer (A1), 40 parts by weight of (meth)acrylic acid ester polymer (B), 20 parts by weight of polypropylene glycol (manufactured by Mitsui Chemicals, Inc.: Actcol P-23K) as a plasticizer, 40 parts by weight of heavy calcium carbonate (manufactured by Maruo Calcium Co., Ltd., product name: NANOX#30) as a filler, 30 parts by weight of precipitated calcium carbonate (manufactured by Shiraishi Industries Co., Ltd., product name: Shirotsuya CCR) as a filler, and titanium dioxide (manufactured by Ishihara Industries Co., Ltd.) as a white pigment. 20 parts by weight of Typeque R-820 (manufactured by Kusumoto Kasei Co., Ltd., product name: Disparon 6500), 1 part by weight of a sagging prevention agent, 1 part by weight of a hindered phenol antioxidant (manufactured by ADEKA Corporation, product name: Adeka Stab AO-60), and 1 part by weight of an amine-based light stabilizer (manufactured by Ouchi Shinko Chemical Co., Ltd., product name: Nocrack CD) were mixed and kneaded thoroughly, and physical dehydration was performed by stirring under reduced pressure at 120°C for 2 hours while mixing. After cooling this to below 40°C, 30 parts by weight of unexpanded thermally expandable particles (C-1), 3 parts by weight of vinyltrimethoxysilane (manufactured by Evonik, trade name: Dynasylan VTMO) as a dehydrating agent, 3 parts by weight of 3-aminopropyltrimethoxysilane (manufactured by Evonik, trade name: Dynasylan AMMO) as an adhesion promoter, and 0.3 parts by weight of dioctyl tin dilaurate (manufactured by Nitto Chemical Co., Ltd., trade name: Neostan U-810) were added and kneaded to obtain a curable composition.

[0071] <Examples 2-6, Comparative Examples 1-5> A curable composition was obtained in the same manner as in Example 1, except that the type and amount of unexpanded thermally expandable particles were changed as shown in Table 1.

[0072] <Examples 7-9, Comparative Examples 6,7> A curable composition was obtained in the same manner as in Example 1, except that the amount of oxyalkylene polymer (A2) added, and the type and amount of unexpanded thermally expandable particles were changed as shown in Table 2.

[0073] [evaluation] <Dumbbell pulling> The curable composition of Example 1 was filled into a mold, cured at 23°C and 50% relative humidity for 3 days, and further at 50°C for 4 days, to prepare a sheet-shaped cured product with a thickness of about 3 mm. The sheet-shaped cured product was punched out into a No. 7 dumbbell shape, and a tensile strength test was performed in an atmosphere of 23°C and 50% relative humidity to measure the elongation at break (%). Hereinafter, the elongation at break measured here is referred to as "initial elongation at break (%)". This measurement was performed using an Autograph (AGS-J) manufactured by Shimadzu Corporation at a tensile speed of 200 mm / min. Further, the sheet-shaped cured product was placed in a constant temperature bath whose internal temperature was previously set to 150°C, taken out after 30 minutes, allowed to return to normal temperature, and then subjected to a tensile strength test in the same manner as described above to measure the elongation at break. Hereinafter, the elongation at break measured here is referred to as "elongation at break after heating (%)". The value obtained by subtracting the initial elongation at break from the elongation at break after heating and dividing by the initial elongation at break was calculated as "elongation at break change rate (%)". Those with an elongation at break change rate of 1% or more were evaluated as "embrittlement" ○, and those with less than 1% were evaluated as "embrittlement" ×. The same test was performed for the curable compositions of Examples 2 to 6 and Comparative Examples 1 to 5.

[0074] <T-peel> Aluminum test specimens were prepared by wiping off dirt and oil with acetyl acetate. The curable composition of Example 7 was uniformly applied to both sides of the test specimen over an area of ​​25 mm in width and 110 mm in length using an applicator stick. After bonding the test specimen coated with the curable composition to the other test specimen, a load was applied to the bonded surface of the test specimens five times with a 5 kg roller. Clamps were installed on both sides and one end of the bonded test specimens to ensure even clamping load. The curable composition was then cured for 3 days at 23°C and 50% relative humidity, and then for another 4 days in an oven at 50°C, for a total of 7 days. The bonded test specimens were subjected to a tensile test, and the peel strength (N) was measured. Hereafter, the peel strength measured here will be referred to as the "initial peel strength (N)". In addition, the cured test specimens were placed in a constant temperature bath preheated to 150°C, removed after 30 minutes, and allowed to return to room temperature. Then, they were subjected to a tensile test in the same manner as above, and the peel strength was measured. Hereafter, the peel strength measured here will be referred to as "post-heat peel strength (N)". The value obtained by subtracting the initial peel strength from the post-heat peel strength and dividing by the initial peel strength was calculated as the "percentage change in peel strength (%)". A peel strength change of 1% or more was classified as "thermally decomposable" (○), and a peel strength change of less than 1% was classified as "thermally decomposable" (×). The same tests were performed on the curable compositions of Examples 5, 8, and 9 and Comparative Examples 5 to 7.

[0075] [Evaluation Results] Table 1 shows the compositions of Examples 1-6 and Comparative Examples 1-5, as well as the evaluation results of the dumbbell tensile tests for these examples and comparative examples.

[0076] [Table 1]

[0077] In Examples 1 to 6, where the curable composition contained 30 parts by weight or more of thermally expandable particles per 100 parts by weight of the total of the oxyalkylene polymer having a reactive silicon group and the (meth)acrylic acid ester polymer having a reactive silicon group, the change in elongation at break was 1% or more in all cases. In Examples 1 to 6, the content of thermally expandable particles was 11% by weight or more relative to the total solid content of the composition.

[0078] On the other hand, in Comparative Examples 1 to 5, which contained 20 parts by weight or less of thermally expandable particles per 100 parts by weight of the total oxyalkylene polymer having a reactive silicon group and the (meth)acrylic acid ester polymer having a reactive silicon group, the change in elongation at break was 0% or less in all cases. In Comparative Examples 1 to 5, the content of thermally expandable particles was less than 11% by weight of the total solid content of the composition.

[0079] In Examples 3 and 4, which included thermally expandable particles (C-1) with an average particle diameter of 9-15 μm, the change in elongation at break was 19% and 29%, respectively, while in Examples 5 and 6, which included thermally expandable particles (C-2) with an average particle diameter of 16-24 μm, the change in elongation at break was 3% and 15%, respectively. Furthermore, in Comparative Examples 1 and 2, which included thermally expandable particles (C-1) with an average particle diameter of 9-15 μm, the change in elongation at break was -7% and 0%, respectively, while in Comparative Examples 3 and 4, which included thermally expandable particles (C-3) with an average particle diameter of 5-9 μm, the change in elongation at break was -6% and -12%, respectively. The comparison between Examples 3 and 4 and Examples 5 and 6, and between Comparative Examples 1 and 2 and Comparative Examples 3 and 4, suggests that the degree of embrittlement due to heating can be controlled by adjusting the average particle diameter of the thermally expandable particles.

[0080] Next, Table 2 shows the compositions of Examples 5, 7-9 and Comparative Examples 5-7, as well as the evaluation results of the T-peel test for these examples and comparative examples.

[0081] [Table 2]

[0082] In Examples 5, 7-9, where the curable composition contained 25 parts by weight or more of thermally expandable particles per 100 parts by weight of the total of the oxyalkylene polymer having a reactive silicon group and the (meth)acrylic acid ester polymer having a reactive silicon group, the peel strength change rate was 1% or more in all cases. In Examples 5, 7-9, the content of thermally expandable particles was 11% by weight or more relative to the total solid content of the composition.

[0083] On the other hand, in Comparative Examples 5 to 7, which contained 20 parts by weight or less of thermally expandable particles per 100 parts by weight of the total oxyalkylene polymer having a reactive silicon group and (meth)acrylic acid ester polymer having a reactive silicon group, the rate of change in peel strength was 0% or less in all cases. In Comparative Examples 5 to 7, the content of thermally expandable particles was less than 11% by weight of the total solid content of the composition.

[0084] From a comparison between Examples 1-6 and Comparative Examples 1-5, and between Examples 5,7-9 and Comparative Examples 5-7, it can be seen that the thermal decomposition properties of the curable composition are good when the content of thermally expandable particles is 25 parts by weight or more per 100 parts by weight of the total oxyalkylene polymer having a reactive silicon group and the (meth)acrylic acid ester polymer having a reactive silicon group, or when the content of thermally expandable particles is 11% by weight or more relative to the total solid content of the composition.

[0085] In Examples 7 and 8, which included an oxyalkylene polymer (A1) with a number average molecular weight of 10,000 or more, in addition to an oxyalkylene polymer (A2) with a number average molecular weight of 5,000 or less, the peel strength change rates were 26% and 36%, respectively, while in Examples 5 and 9, which did not include the oxyalkylene polymer (A2), the peel strength change rates were 10% and 11%, respectively. From the comparison between Examples 7 and 8 and Examples 5 and 9, it can be seen that the thermal decomposition properties of the curable composition are good when the oxyalkylene polymer is a mixture containing a polymer with a number average molecular weight of 10,000 or more and a polymer with a number average molecular weight of 5,000 or less.

Claims

1. (A) Oxyalkylene polymer having a reactive silicon group, (B) (meth)acrylic acid ester polymers having reactive silicon groups, and (C) Unexpanded thermally expandable particles It contains, The content of (C) is 25 parts by weight or more with respect to a total of 100 parts by weight of (A) and (B). Curable composition.

2. The curable composition according to claim 1, wherein (C) is a thermally expandable microcapsule in which a volatile expanding agent is encapsulated in the outer shell.

3. The curable composition according to claim 1, wherein the expansion initiation temperature of (C) is 70°C or higher.

4. The curable composition according to claim 1, wherein the average particle size of (C) is 9 μm or more.

5. The curable composition according to claim 1, wherein the average particle size of (C) is 24 μm or less.

6. The curable composition according to claim 1, wherein the content of (C) is 80 parts by weight or less with respect to a total of 100 parts by weight of (A) and (B).

7. The curable composition according to claim 1, wherein (A) is a mixture comprising a polymer (A1) having a number average molecular weight of 10,000 or more and a polymer (A2) having a number average molecular weight of 5,000 or less.

8. The curable composition according to claim 7, wherein the weight ratio of (A1) to (A2) is 5:95 to 95:

5.

9. A cured product obtained by curing a curable composition according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Composition comprising a moisture-crosslinkable polymer

    WO2024132795A1